Metal and organic pollutants bioremediation by extremophile microorganisms - Giovanella, Patricia [UNESP]; Vieira, Gabriela A. L. [UNESP]; Ramos Otero, Igor V. [UNESP]; Pellizzer, Elisa Pais [UNESP]; Fontes, Bruno de Jesus [UNESP]; Sette, Lara D. [UNESP] (Elsevier B.V., 2020)
Extremophiles comprise microorganisms that are able to grow and thrive in extreme environments, including in an acidic or alkaline pH, high or low temperatures, high concentrations of pollutants, and salts, among others. These organisms are promising for environmental biotechnology due to their unique physiological and enzymatic characteristics, which allow them to survive in harsh environments. Due to the stability and persistence of these microorganisms under adverse environmental conditions, they can be used for the bioremediation of environments contaminated with extremely recalcitrant pollutants. Here, we provide an overview of extremophiles and the role of omics in the field of bioremediation of environmental pollutants, including hydrocarbons, textile dyes and metals.
Keywords: Environmental biotechnology; Hydrocarbons; Polycyclic aromatic hydrocarbon; Metals; Textile dyes